Photoacoustic wave dynamics in magneto-hydro-semiconductor media with rotation and multi-temperature effects - M. Adel; Shreen El-Sapa; Alaa A. El-Bary; Khaled Lotfy; Engin Can (Case Studies in Thermal Engineering)
This study presents a comprehensive analytical model to investigate wave propagation phenomena in magneto-hydro-semiconductor materials under the combined influences of a rotational field and multi-temperature effects. The motivation stems from the need to understand complex wave interactions in advanced materials used in optoelectronic, sensing, and energy applications, where mechanical, thermal, and electromagnetic effects are strongly coupled. By incorporating rotational dynamics and magnetic field effects into a photoacoustic framework, the model captures the influence of Coriolis and Lorentz forces alongside distinct thermal behaviors of multi-phase systems. Utilizing the normal mode method, the coupled system of equations governing motion, energy, and electromagnetic fields is solved analytically. The study offers novel insights into how rotation and magnetic field strength affect photoacoustic wave characteristics, including thermal relaxation and stress distribution. Graphical results reveal critical trends in physical field profiles, demonstrating the model's potential for guiding the design of high-performance semiconductor-based devices operating under dynamic field conditions.